Plurihormonal Cosecretion by a Case of Adrenocortical Oncocytic Neoplasm - J. J. Corrales; C. Robles-Lázaro; A. I. Sánchez-Marcos; M. C. González-Sánchez; P. Antúnez-Plaza; J. M. Miralles (Case Reports in Endocrinology)
Adrenocortical oncocytic neoplasms (oncocytomas) are extremely rare; only approximately 159 cases have been described so far. The majority are nonfunctional and benign. We describe an unusual case of a functional oncocytoma secreting an excess of glucocorticoids (cortisol) and androgens (androstenedione and DHEAS), a pattern of plurihormonal cosecretion previously not reported in men, presenting with endocrine manifestations of Cushing’s syndrome. The neoplasm was considered to be of uncertain malignant potential (borderline) according to the Lin-Weiss-Bisceglia criteria.